PD‐L1 expression and CD8‐positive T cells are associated with favorable survival in HER2‐positive invasive breast cancer. Issue 6 (19th September 2018) - Hou, Yanjun; Nitta, Hiroaki; Wei, Lai; Banks, Peter M; Lustberg, Maryam; Wesolowski, Robert; Ramaswamy, Bhuvaneswari; Parwani, Anil V.; Li, Zaibo
Abstract: Programmed cell death 1 (PD‐1) and its ligand (PD‐L1) are key physiologic suppressors of the cytotoxic immune reaction. However, to date, the combination of PD1/PD‐L1 expression and tumor‐infiltrating lymphocytes (TILs) and antigen‐presenting cells has been only minimally reported in breast carcinoma, in particular in relation to HER2‐positive cases. The goal of this study was to evaluate both cellular tumoral immune reaction and PD‐L1/PD1 distribution in HER2‐positive cases, as well as any associations with clinical outcome using conventional chemotherapy combined with HER2 blocking. Multicolor immunohistochemical multiplex assays simultaneously demonstrating PD1, PD‐L1, and CD8 or PD‐L1, CD3, and CD163 were performed on tissue microarrays (TMA) representing 216 pretreatment cases of HER2‐positive invasive breast carcinoma. PD‐L1 expression was identified in 38 cases (18%), including 12 cases (6%) with PD‐L1 labeling of tumor cells and 26 cases (12%) with PD‐L1 labeling of immune cells only. Ten of 12 cases with PD‐L1 staining of tumor cells showed staining of associated immune cells as well. With this assay method, PD1 was detectable in many fewer cases (6 cases or 3%). PD‐L1 expression was positively associated with high Nottingham grade, negative ER and PR, the absence of lymph node metastasis, and high levels of CD8 + cells. The overall survival by univariate analysis was positively associated with lower tumor stage, the absence of lymph node metastasis, PD‐L1 expression, and high levels of CD8 + cells. Therefore, our data suggest cytotoxic immune reaction mediated by CD8‐positive T cells and PD‐L1 expression may predict a better outcome in patients with HER2‐positive breast carcinoma managed with conventional chemotherapy and HER2‐blocking therapy. These findings recommend clinical trials utilizing checkpoint blocking immunotherapy in some form for HER2‐positive breast cancer.